Faktor yang Berhubungan dengan Kepadatan Jentik Aedes Aegypti - Iriani, Agnes Intan; Siwiendrayanti, Arum (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Dengue Hemorrhagic Fever (DHF) is a health problem that has the potential to spread disease. Based on data from the Semarang City Health Office, it has been found that the number of DHF cases in the Tembalang Sub-district Elementary School Area with an age group <15 years is 22 cases in 2021, and 28 cases in July 2022. The purpose of this study was to determine the factors associated with larval density. Aedes aegypti in Elementary Schools Tembalang Sub-District, Semarang City. Methods: This type of research is analytic observational through a cross sectional approach. The research sample was 48 elementary schools with a total sampling technique. Research instrument using a questionnaire and observation sheet. Data were analyzed using the Chi-Square test. Results: Statistical tests showed that the variable color of the container (p=0.031), level of knowledge of cleaning staff (p=0.007), type of container (p=0.683), and population density (p=0.765). Conclusion: This study shows that there is a relationship between the color of the container and the level of knowledge of the cleaning staff, and there is no relationship between the type of container and population density and the density of Aedes aegypti larvae in Elementary Schools Tembalang Sub-District, Semarang City.